Models of multi-agent decision making - Zappala, Julian (2014)
In this thesis we formalise and study computational aspects of group decision making for rational, self-interested agents. Specifically, we are interested in systems where agents reach consensus according to endogenous thresholds. Natural groups have been shown to make collective decisions according to threshold-mediated behaviours. An individual will commit to some collective endeavour only if the number of others having already committed exceeds their threshold. Consensus is reached only where all individuals express commitment. We present a family of models that describe fundamental aspects of cooperative behaviour in multi-agent systems. These include: coalition formation, participation in joint actions and the achievement of individuals’ goals over time. We associate novel solution concepts with our models and present results concerning the computational complexity of several natural decision problems arising from these. We demonstrate potential applications of our work by modelling a group decision problem common to many cohesive groups: establishing the location of the group. Using model checking tools we compute the effects of agents’ thresholds upon outcomes. We consider our results within an appropriate research context.